Inflation, inflation uncertainty and output in Tunisia - Ahmed Hachicha; Lean Hooi Hooi (Kiel Institute for the World Economy (IfW), 2013)
This study investigates the relationship between inflation, inflation uncertainty and output in Tunisia using real and nominal data. GARCH-in-mean model with lagged variance equation is employed for the analysis. The result shows that inflation uncertainty has a positive and significant effect on the level of inflation only in the real term. Moreover, inflation uncertainty Granger-causes inflation and economic growth respectively. These results have important implications for the monetary policy in Tunisia.
Keywords: C22; E31; 330; GARCH-M model; inflation; inflation uncertainty; output